BS EN IEC 61753-051-02. Fibre optic interconnecting devices and passive components. Performance standard. Part 051-02. Plug-receptacle style single-mode fibre fixed optical attenuators for category C. Controlled environments (28th May 2021) - British Standards Institution
No abstract available